2020
DOI: 10.24156/jikk.2020.13.3.199
|View full text |Cite
|
Sign up to set email alerts
|

Gender Analysis of Child Investment and Child Quality Among Farmer Families in Indonesia

Abstract: Families have obligations to protect and care for their children. The general objective of this study was to analyze the gender of the investment and the quality of the children in highland farmers. The study was conducted at highland areas at Cianjur Regency (Sindangjaya Village, Cipanas Sub-district) and Bogor Regency (Petir Village, Dramaga Sub-district). The findings showed that they were 4 (four) indicators of child investment latent variable such as the allocation of time togetherness between parents and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 192 publications
0
2
0
Order By: Relevance
“…Reproductive activity covers cooking, shopping, cleaning the house, washing clothes, and caring for children. Social activity includes recitation, helping with celebrations, farmer group meetings, and community service (Puspitawati, 2012). The division of labour through productive, reproductive, and social activities can provide an overview of how men and women divide their roles in the household (Nurmayasari et al, 2019).…”
Section: Enhance Labor Optimization To Increases Potato Productionmentioning
confidence: 99%
“…Reproductive activity covers cooking, shopping, cleaning the house, washing clothes, and caring for children. Social activity includes recitation, helping with celebrations, farmer group meetings, and community service (Puspitawati, 2012). The division of labour through productive, reproductive, and social activities can provide an overview of how men and women divide their roles in the household (Nurmayasari et al, 2019).…”
Section: Enhance Labor Optimization To Increases Potato Productionmentioning
confidence: 99%
“…In this case, the structure and organization of the family is the main factor in family functioning, namely in influencing and determining the behavior of family members. Puspitawati (2012) revealed that the division of roles between husband and wife in carrying out family functions does not only include cleaning the house, cooking, washing clothes, and the like others but also includes caring for children, such as accompanying children to study and play. Attention, affection, and parenting style applied by parents to children will affect the growth and development of children in the future.…”
Section: Introductionmentioning
confidence: 99%